New records of ring nematodes, Bakernema enormese n. sp. and Criconema (Nothocriconemella) graminicola Loof, Wouts & Yeates, 1997 (Nematoda: Criconematidae) from natural forests of Vietnam - Chau, Nguyen Ngoc (Academia Journal of Biology, 2019)
Bakernema enormese sp. n., collected from rhizosphere of forest wood trees in Muong Phang, Dien Bien Province (north Vietnam) is described and illustrated. The new species is characterized by large body size and stylet. In general, this new species is close to two existing species of the same genus, B. inaequale and B. dauniense by cuticle structure in transparent membranous projections which appear in lateral view as spine-like structures on each annulus. These structure arranged into several rows along the body. In morphology, the new species differs from B. inaequale and B. dauniense  by body and stylet length, i.e. 609–842 µm and 143.5–150 µm vs. 391–578 µm and 59–74 µm for B. inaequale and vs. 391–461 µm and 65–74 µm for B. dauniense. In addition, new species can be distinguished from B. inaequale by the longer membranous projection, 8–12 vs. 6–10 µm and vagina shape, curved vs. sigmoid. From B. dauniense, the new species differs by the much longer membranous projection, 8–12 vs. 1.4–2.2 µm and less number annules between vulva and tail end (RV), 3–4 vs. 7.8 annules. The presence of Criconema (Nothocriconemella) graminicola Loof, Wouts & Yeates, in Vietnam with morphometrics, illustrators and remarks given